PERCEIVED DIFFERENCES IN VR EXPERIENCES: A GENDER-BASED ANALYSIS OF ADOPTION AND ENGAGEMENT - Victoria Olubola Adeyele (Jurnal Eduscience)
This study explores the perceived differences in Virtual Reality (VR) experiences and engagement between boys and girls in an educational context. Utilizing the VR Learning Experience Gender Survey (VRLEGS), data were collected from 44 pupils, comprising 23 boys and 21 girls, following their exposure to various educational VR applications. The study revealed no significant differences between the genders in terms of VR adoption and engagement. The findings align with previous research indicating that while gender can influence technology adoption and usage, the differences are not always significant and can be influenced by various factors such as cultural context and social support. The results suggest that boys and girls perceive and engage with VR technology, similarly, highlighting the potential for VR as an inclusive educational tool. In conclusion, the study demonstrates that VR technology can be effectively utilized in educational settings without significant gender disparity. It is recommended that educators and policymakers continue to integrate VR into curricula, ensuring equal access and support for all students.